Totally implantable venous access devices – clinical use - Goździk, Joanna (Przewodnik Lekarza/Guide for GPs Supplement, 2007)
Totally implantable venous access devices (TIVDs) significantly contribute to the treatment of patients requiring long-term chemotherapy, total parenteral nutrition, fluid replacement, and repeated courses of intravenous antibiotics. TIVDs considerably improve the quality of life for these patients by giving them unrestricted ability and freedom in their choice of activities. However, many complications have been reported to be associated with TIVDs.